Risk of injury after emergency department visit for acute peripheral vertigo: a matched-cohort study - Hayoung Kim; Sihyoung Lee; Joonghee Kim (Clinical and Experimental Emergency Medicine, 2020)
Objective Peripheral vertigo is one of the most common causes of the emergency department (ED) visits. It can impair balance and might predispose patients to injuries after discharge. The purpose of this study was to determine whether peripheral vertigo is associated with an increased risk of trauma. Methods This matched-cohort study used the nationally representative dataset of de-identified claim information of 1 million randomly sampled individuals from a real Korean population, from 2002 to 2013. The exposure cohort included patients who visited EDs for new-onset peripheral vertigo without prior or concurrent injury. Each patient was randomly matched to five unexposed individuals (also without previous injury) by incidence density sampling. The primary outcome was a new injury within 1 year. The secondary outcomes were various injury subtypes. The time-dependent effect of the exposure was modeled using the extended Cox model. Age, sex, comorbidities, and household income level were included as covariates. Results A total of 776 and 3,880 individuals were included as the exposure and comparison cohorts, respectively. The risks of trunk injury and upper extremity injury were significantly higher in the exposure cohort. Extended Cox models with multivariable adjustment showed significantly increased risk for up to 1 year, with the first 1-month; 1 month to 3 months; and 3 months to 1 year hazard ratios of 5.23 (95% confidence interval [CI], 2.83–9.64); 1.50 (95% CI, 1.02–2.20); and 1.37 (95% CI, 1.11–1.68), respectively. Conclusion Patients visiting EDs for acute peripheral vertigo are at a higher risk of a new injury for up to a year.